Bridging the gap: How human-centered design can help unlock bottlenecks in the diffusion of small-scale irrigation in Nigeria - Balana, Bedru; Abba, Aminu; Iraoya, Augustine Okhale; Yakasai, Musa Tukur; Yakasai, Bello; Abdullahi, Kabiru; Shuaibu, Ahmed Usman; Musa, Nuruddeen Muhammad; Kirui, Oliver K.; Edeh, Hyacinth O.; Ringler, Claudia (International Food Policy Research Institute, 2025)
Ample evidence shows that small-scale irrigation (SSI) has positive impacts on agricultural productivity, poverty reduction, climate resilience and household food security, nutrition. Despite this, adoption of SSI has remained low in sub-Saharan Africa, including Nigeria, where previous research suggests potential for adoption is largest. Factors such as high cost of technologies, farmers’ risk behavior, lack of incentives, and lack of access to finance and capacity gaps have often been noted as key constraints limiting the adoption/scaling of SSI among smallholders. However, in an environment with low overall levels of use, it is important to not only focus on the challenges experienced by smallholder farmers, but also on those of key intermediary actors—specifically government, irrigation equipment distributors, and finance institutions—that are critical for a supportive enabling environment of SSI technology diffusion. To understand the constraints these groups encounter and propose innovative policy, financial, and supply chain solutions, we conducted a series of human-centered design (HCD) workshops in three locations in Nigeria. Key solutions proposed during nine workshops include the need for cross-sector coordination and policy harmonization, improved data and digital systems and platforms, customized financial products and risk-sharing options for SSI, capacity-sharing for extension services, and specific strategies to support women farmers so that they benefit equally.